Using the (im)materialities framework to trace the contrapuntal lines of allegiance and belonging for globally mobile children. Issue 4 (4th July 2018) - Hannaford, Jeanette
ABSTRACT: This paper discusses the use of Burnett, Merchant, Pahl and Rowsell's (im)materiality literacy analysis framework to explore online and offline literacies in the lives of globally mobile children. The voices of these children have been little explored in New Literacies research. Globally mobile 'third culture' children who attend International Schools are often foreigners where they live, yet have multiple sites of belonging, including digital worlds. In analysing the abundant data of a year-long multicase study, the theoretical lenses of spatiality, mediation, materiality, and embodiment, as proposed in Burnett el al.'s framework, provided a productive framework through which to explore the complicated intersections of literacy, identity, and digital worlds in these children's lives. The paper demonstrates how the framework might be applied, focusing on two of the children in the study. Prompted by insights provided by the (im)materiality framework, a contrapuntal metaphor is proposed as a way to understand allegiance and belonging in the lives of these globally mobile children.